Gestão de resíduos sólidos nos centros urbanos brasileiros: evolução, desafios e tendências - Bezerra, Yuri de Santana (2023)
Urban centers present an increasingly latent and irremediable problem: the problem of “waste”. The increasingly accentuated production of solid waste in these centers presents a major challenge for several sectors, directly or indirectly linked to the provision of solutions that aim to transform this problem into an opportunity. It is important to highlight that solid waste management is a multidisciplinary field, which involves knowledge in several areas, such as environmental engineering, urban planning, economics, public policies, law, chemistry, engineering, as well as administration. It is therefore from a management perspective that this scientific research is developed. The objective of this work was to analyze the development of solid waste management in urban centers in the national context in compliance with what occurs internationally. The research, in terms of its approach, is characterized as qualitative, and in terms of its objectives, the present work stands out as an exploratory and descriptive study. The methodology will be the application of a focus group with several experts, from different areas of activity, including municipal waste managers, recycling entrepreneurs and university professors. The focus group is a research technique that seeks to identify trends and conclusions based on the opinion of experts on the subject, and is recommended for the participatory construction of knowledge based on the experience of the main actors and participants on the topic. The study shows, from the point of view of the evolution of management in the Brazilian context, that we are still far behind in relation to developed nations, but also that there have been developments, many of them caused by the establishment of the National Solid Waste Policy (PNRS) of 2010. However, the implementation of all the purposes proposed by the legislation still appears to be a distant reality. Other research contributions of similar importance highlight the low diversification of the Brazilian waste management matrix, with the landfill as an almost exclusive form of disposal, in addition to the absence of integrated waste management, which aims at the joint participation of public authorities and private. The results of this research contribute to understanding the current panorama of solid waste management more broadly, identifying challenges faced by waste management in Brazilian cities, in addition to pointing out possible solutions to address this problem in the future.